1991
DOI: 10.1007/bf02540221
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of diffusion and reaction rates in anaerobic microbial aggregates

Abstract: The ability of hydrogen diffusion to account for the rates of methane production in microbial aggregates was studied in a defined coculture consisting of a sulfate reducer grown as a syntrophic hydrogen producer in the absence of sulfate and a methanogen. The hydrogen uptake kinetics of the methanogen were determined using the infinite dilution technique. The maximum hydrogen uptake velocity was 7.1 nmol/min/μg protein and the half saturation constant for hydrogen uptake was 386 nmol/liter. A threshold of 28 n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Strong (1987, 1991) demonstrated that nitrifica tion rates were higher with increased mixing intensity in activated sludge and posited that the governing mechanism was a decrease in floe size that reduced mass-transfer resistance. Goodwin et al (1991) used successfully a diffusion model to describe the kinetics of methane production in an anaerobic digester using an intrinsic half-saturation coefficient for hydrogen that was an order of magnitude lower than typical literature values. Lotti et al (2014) showed that the half saturation coefficient for nitrite in their enriched anammox culture was a function of mean aggregate size and further showed that the intrinsic K0 was extremely low (0.035 mg/L compared to a range of 0.1 to 2.3 mg/L for the extant I<s).…”
Section: Discussionmentioning
confidence: 99%
“…Strong (1987, 1991) demonstrated that nitrifica tion rates were higher with increased mixing intensity in activated sludge and posited that the governing mechanism was a decrease in floe size that reduced mass-transfer resistance. Goodwin et al (1991) used successfully a diffusion model to describe the kinetics of methane production in an anaerobic digester using an intrinsic half-saturation coefficient for hydrogen that was an order of magnitude lower than typical literature values. Lotti et al (2014) showed that the half saturation coefficient for nitrite in their enriched anammox culture was a function of mean aggregate size and further showed that the intrinsic K0 was extremely low (0.035 mg/L compared to a range of 0.1 to 2.3 mg/L for the extant I<s).…”
Section: Discussionmentioning
confidence: 99%
“…In other natural ecosystems producing CH 4 , like anaerobic soil or rumen, there is also little H 2 emission (Wolin 1980;Conrad & Babbel 1989), because H 2 is ef®ciently transferred from H 2 -producing microorganisms to H 2 -consuming methanogens. Such a low concentration of H 2 may be achieved by methanogens surrounding H 2 producers (Goodwin et al 1991). As observed in R.¯avipes and R. speratus, methanogens on the gut wall are possibly inef®cient to receive H 2 ; consequently the H 2 emission rate may be higher than that observed in N. koshunensis in which methanogens exist inside the H 2 producers, protozoa, as an intracellular symbiont.…”
Section: Locality Of H 2 Producers and Methanogensmentioning
confidence: 92%
“…Such a ratio of CH 4 /H 2 possibly re¯ects the ef®ciency of interspecies transfer of H 2 in the system. Hydrogen is an important intermediate metabolite, but its concentration is usually very low (Lovley & Goodwin 1988;Goodwin et al 1991). In other natural ecosystems producing CH 4 , like anaerobic soil or rumen, there is also little H 2 emission (Wolin 1980;Conrad & Babbel 1989), because H 2 is ef®ciently transferred from H 2 -producing microorganisms to H 2 -consuming methanogens.…”
Section: Locality Of H 2 Producers and Methanogensmentioning
confidence: 99%
“…Similar results has been obtained with a more energetic substrate such as lactate in a defined coculture. 20 No attempt was made to measure formate during these experiments, and the possibility of formate being an electron carrier between the syntrophic partners in our system cannot be ruled out. Nonetheless, formate is not necessary to account for the observed rates of interspecies electron transfer in our system.…”
Section: Discussionmentioning
confidence: 96%